Pricing ArcelorMitall steel globally : the effects of currency changes - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
International companies can often face marketing challenges as a result of the intricacies of international finance. This case study focuses on ArcelorMittal, the world's largest steel manufacturer, and the pricing challenges that the company faces due to ever changing exchange rates and fluctuating costs.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Pricing ArcelorMitall Steel Globally: The Effects of Currency Changes. In International marketing (pp. 335-336). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; ArcelorMittal (Firm); Steel -- Prices -- Case studies; Foreign exchange rates -- Case studies